2022
DOI: 10.1007/s10211-022-00400-6
|View full text |Cite
|
Sign up to set email alerts
|

Poison frog social behaviour under global change: potential impacts and future challenges

Abstract: The current and cascading effects of global change challenges the interactions both between animal individuals (i.e. social and sexual behaviour) and the environment they inhabit. Amphibians are an ecologically diverse class with a wide range of social and sexual behaviours, making them a compelling model to understand the potential adaptations of animals faced with the effects of human-induced rapid environmental changes (HIREC). Poison frogs (Dendrobatoidea) are a particularly interesting system, as they dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 172 publications
0
2
0
Order By: Relevance
“…It is geographically and taxonomically widespread (e.g. great tits Parus major Charmantier et al, 2008; black bears Ursus americanus Johnson et al, 2020; poison frogs (Dendrobatoidea) Justicia et al, 2022). Responses mediated via parental effort have been best documented in birds, particularly colonially breeding species with restricted foraging ranges and energetically expensive foraging methods, and parental effort is widely used as a ‘barometer’ of changes in environmental conditions (Burger & Piatt, 1990; Fayet et al, 2021; Harding et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It is geographically and taxonomically widespread (e.g. great tits Parus major Charmantier et al, 2008; black bears Ursus americanus Johnson et al, 2020; poison frogs (Dendrobatoidea) Justicia et al, 2022). Responses mediated via parental effort have been best documented in birds, particularly colonially breeding species with restricted foraging ranges and energetically expensive foraging methods, and parental effort is widely used as a ‘barometer’ of changes in environmental conditions (Burger & Piatt, 1990; Fayet et al, 2021; Harding et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, given the importance of amphibians as ecological indicators of environmental disturbance, more studies should investigate the effects of global change on the different forms of care ( Schlippe Justicia et al 2022 ). While it has been previously reported that hostile environments do not seem to be associated with any specific type of care ( Vági et al 2020 ), current trends of climate change and habitat destruction may yet render this finding obsolete.…”
Section: Future Directions In the Study Of Amphibian Parental Carementioning
confidence: 99%